2008
DOI: 10.2174/1874279300802010045
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of the Vaginal Flora at First Prenatal Visit is Associated with Preterm Delivery and Low Birth Weight

Abstract: Abstract:Objective: Can assessment of vaginal microbial flora at first prenatal visit predict the outcome of pregnancy?Material and methods: Pap smears and vaginal cultures were taken from 222 pregnant women at their first prenatal visit. Lactobacillary grades (LBG I-III) on Pap smears were used as a basis for the scoring. Points were added or subtracted according to the morphotypes of the lactobacilli, the presence of abnormal cellular morphology, increased vaginal leukocytosis, visible pathogens or red blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
5
10
0
Order By: Relevance
“…6 Donders also records abnormal status of lactobacilli, that is, their absence, which is a negative factor and enables development of infection, especially in pregnancy. [7][8][9][10][11] In our study most common organism is the E. Coli amounting 34% followed by Candidial spp. 21%.…”
Section: Discussionsupporting
confidence: 49%
“…6 Donders also records abnormal status of lactobacilli, that is, their absence, which is a negative factor and enables development of infection, especially in pregnancy. [7][8][9][10][11] In our study most common organism is the E. Coli amounting 34% followed by Candidial spp. 21%.…”
Section: Discussionsupporting
confidence: 49%
“…Not only BV, but also aerobic vaginitis in early pregnancy is linked to preterm deliveries and chorionamnionitis (Rezeberga et al, 2008;Donders et al, 2008;. Since the extent of the inflammatory reaction has a particularly important role in the pathogenesis of preterm deliveries (Jacobson et al, 2003), the association of E. coli in the presence of leucocytosis found in our study can be important.…”
Section: Discussionsupporting
confidence: 53%
“…Although there is strong evidence that microscopic findings indicating abnormal vaginal microflora (AVM) are associated with complications in pregnancy, such as preterm birth, chorionamnionitis and preterm rupture of the membranes (Hay et al, 1994;Donders et al, 2008), there is no consensus on using culture results as a substitute for these findings. We strongly object to start treatment based solely on culture of vaginal microorganisms, as this leads to overtreatment, exposes the mother and foetus to unnecessary toxins, increases the risk of bacterial antimicrobial resistance in both mother and new-born, and enhances the risk of hard to treat, recurrent vulvovaginal candidosis, along with other disturbances of the vaginal ecology.…”
Section: Introductionmentioning
confidence: 99%
“…AV elicits an intense immune response with high levels of interleukin-6, interleukin-1 ␤ and leukemia inhibitory factor in the vaginal fluid [11,13] , and may be a potential cofactor in the pathogenesis of infection-related complications in pregnancy such as cervix shortening, chorioamnionitis, preterm rupture of the membranes and preterm delivery [15][16][17] . Although some treatment trials have shown some success with topical antibiotics like kanamycin, standard therapy is not yet available for AV [18,19] .…”
mentioning
confidence: 99%